Data protection in the European Union 1 - Krajewska, Atina (Henry Stewart Talks, 2015)
The complex system of data protection laws, Data protection in the EU, General personal data processing principles, Directives and regulations, The data subject (Personal & sensitive data), Lack of clarity in personal data definition